Identification of liability-related impediments to sharing §409 safety data among transportation agencies and a synthesis of best practices. - Cambridge Systematics; American Automobile Association; National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board (Washington, D.C. Transportation Research Board, 2006)
"This digest presents the results of NCHRP Project 8-54, "Identificaiton of liability-related impediments [section]409 safety data among transportation agencies and s synthesis of best practices." The research project was conducted by Cambridge Systematics, Inc., with support from the American Automobile Association."
Caption title.
"October 2006."
Includes bibliographical references (p. 11).
Also issued online.
Keywords: Transportation agencies -- United States -- Data processing; Traffic accidents -- United States -- Statistics -- Data processing; Interorganizational relations; Knowledge management